Comparison of Adult Testis and Ovary MicroRNA Expression Profiles in Reeves’ Pond Turtles (Mauremys reevesii) With Temperature-Dependent Sex Determination - Xiong, Lei; Yang, Mengli; Zheng, Kai; Wang, Ziming; Gu, Shengli; Tong, Jiucui; Liu, Jianjun; Shah, Nadar Ali; Nie, Liuwang (Frontiers in Genetics, 2020)
Gonadal functional maintenance and gametogenesis comprises a highly regulated and coordinated biological process, and increasing evidence indicates that microRNAs (miRNAs) may be involved in this dynamic program. In Reeves’ pond turtle (Mauremys reevesii) with temperature-dependent sex determination (TSD), some differentially expressed genes (DEGs) that encode key enzymes involved in steroidogenic biosynthesis (CYP19A1) and key molecules related to gonadal functions (DMRT1, SOX9, AMH, FOXL2, WNT4, RSPO2, and GDF9) were identified in previous adult gonadal RNA-seq studies. However, it is not clear how the regulatory network comprising miRNAs changes the expression levels of genes related to gonadal functional maintenance and gametogenesis. In this study, miRNA sequencing of adult testis and ovary tissues from M. reevesii detected 25 known and 379 novel miRNAs, where 60 miRNAs were differentially expressed in the testis and ovary. Ten differentially expressed miRNAs were validated by quantitative reverse transcription real-time PCR. 1,477 target genes based on the differentially expressed miRNAs were predicted, where 221 target genes also exhibited differential expression. Moreover, several miRNA/target gene pairs, i.e., mre-let-7a-5p/mre-let-7e-5p and CYP19A1, mre-miR-200a-3p and DMRT1, mre-miR-101-3p and SOX9, and mre-miR-138-5p and AMH were identified. To explore the regulatory role of miRNAs, we conducted target gene enrichment analysis for the miRNAs and 221 target genes in the regulatory network, and compared the signaling pathways related to gonadal functional maintenance and gametogenesis between the DEGs and target genes. Our findings provide crucial information to facilitate further research into the regulatory mechanisms involving miRNAs in turtle species with TSD.